PENGARUH PENDIDIKAN DAN LATIHAN TERHADAP KOMPETENSI GURU DAN KOMITMEN KERJA GURU SERTA DAMPAKNYA TERHADAP KUALITAS PENDIDIKAN DI SMA NEGERI SE KECAMATAN DEMAK KABUPATEN DEMAK - Hendrajaya Hendrajaya (JURNAL ILMIAH EDUNOMIKA, 2022)
To increase the educational quality, it was needed the teacher’s competence, the work teacher’s work commitment, and the training and education. The purpose of this research was to explain the influence of the training and education toward teachers’ competence and teahers’ work commitment and the effect on educational quality in Demak Subdistrict, Demak Regency. The research was conducted by using the quantitative method, inferential type. The research was conducted on 65 teachers of State Senior High School in Demak Subdistrict, Demak Regency. The technique of data collection was using questionnaire and analyzed by using SPSS for windows version 17.0. The result of this research showed that (a) the training and education program influenced teachers’ competence, (b) the training and education influenced teachers’ work commitment, (c) the training and education influenced educational quality, (d) teachers’ competence influenced educational quality, (e) teachers’ work commitment influenced educational quality, (f) teachers’ competence did not mediate the effect of the training and education on educational quality, (g) teachers’ work commitment did not mediate the effect of the training and education on educational quality. Keywords : Training and Education, Teachers’ Competence, Teachers’Work Commitment, Educational Quality